Application of a 2D-Hydrodynamic Model to Assess the Impact of Spring Water Discharge into the Lake Pamvotida in Ioannina, Greece - Zachopoulos, K.; Papadimos, D. (2025)
p. 645-646 In: Proceedings of the 13th World Congress of EWRA on Water Resources and Environment, Palermo, Italy 24 - 28 2025.